Public first aid education model design study based on user experience - Luo, Jing; Zheng, Kaiqiao; Hong, Wudi (Frontiers in Public Health, 2023)
The public first aid penetration rate is an important indicator of the level of civilization in modern society. China's current first aid penetration rate is relatively low. There is still great room for improvement in the first aid education model. In this study, we focused on user experience, using interviews to gain insight into participants' detailed experiences during first aid learning. We analyzed the interviews using NVivo and identified targeted design strategies. The results show that the use of familiar music has a significant positive effect on participants' willingness and confidence to learn, while fear of teaching aids has no effect on willingness and confidence. Based on the design strategy, we proposed a "feedback device + app" approach to enhance the public's first aid knowledge and skills. Finally, a satisfaction survey was conducted through a scale questionnaire, and the results showed that the user experience-based first aid education model can better meet the public's learning needs for first aid knowledge and skills.